Expenditure reform in industralised countries: a case study approach - Sebastian Hauptmeier; Martin Heipertz; Ludger Schuknecht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This study examines reforms of public expenditure in industrialised countries over the past two decades. We distinguish ambitious and timid reformers and analyse in detail reform experiences in eight case studies of ambitious reform episodes. We find that ambitious reform countries reduce spending on transfers, subsidies and public consumption while largely sparing education spending. Such expenditure retrenchment is also typically part of a comprehensive reform package that includes improvements in fiscal institutions as well as structural and other macroeconomic reforms. The study finds that ambitious expenditure retrenchment and reform coincides with large improvements in fiscal and economic growth indicators.
Keywords: O57; H6; H5; 330; public expenditure; expenditure reform; economic growth; deficit; debt; employment; case studies; fiscal institutions